Dehesas y paisajes adehesados en Castilla y León (Polígonos. Revista de Geografía, 2012)
The "dehesas" of Castile and Leon occupy about 5.5% of the regional territory, primarily concentrated in the southwestern sector, the provinces of Salamanca, Avila and Zamora. They show a remarkable variety of lithological substrates, and the Holm oak is the most common tree species in these open woodlands. The farms are large (between 350 and 400 ha on average) and the land tenure is majority ownership. In this farms the livestock is the fundamental production, because it represents just over 75% of income. The dependence on subsidies is now considerable, as with other types of farms. Fattening Iberian pigs and cattle breeding are the main uses, and agricultural and forest uses are subordinate to the grazing. The landscape of this agricultural system is characterized by the prominence of open oak woodland with varying degrees of density. In recent years it has greatly increased the stocking density, and this, coupled with other processes are adversely affecting the internal balance of these agro-ecosystems and their own persistence, primarily because of problems related to a proper state of the trees